Selected aspects of the health condition of hospitalised soldiers after military action and the manifestation of externalising anger - Ortenburger, Dorota E.; Wąsik, Jacek; Tsos, Anatolii; Andrijchuk, Olga; Bielikowa, Natalia; Indyka, Svitlana (My University, 2019)
Introduction: Participation in defensive war actions is connected with the necessity of dealing with different difficult mental and health consequences. Aim of the research: To obtain knowledge concerning typical manifestations of externalising anger in everyday situations by the hospitalised participants of antiterrorist operations, who suffered from posttraumatic stress and whose health worsened. Material and methods: The research covered 35 hospitalised participants of military action during antiterrorist operations (age: 34.61 ±9.23 years; range: 21–56 years) in hospitals in Lutsk. The data were obtained with the application of the questionnaire within health psychology, the Anger Expression Scale, and data from the existing documentation. Results: An image composed of many symptoms was more frequent than a single symptom, which makes us think that we can talk about the appearance of the phenomenon of multiple morbidities in the case of the participants of military actions. There is a slight interdependency between the value of an index of the registered systolic blood pressure of the hospitalised participants of military action and the tendency to express anger (r = 0.41). The value of the correlation index between the willingness to act in retaliation and the registered blood pressure was r = 0.58 (p < 0.05). The value of the index of the summary level of externalised anger revealed in typical situations was 24.37 ±6.33 (scores in the scale 10–50). Partial manifestations of externalising anger included raising one’s voice as a reaction to shouting 3.06 ±1.08, anger caused by waiting 2.97 ±1.22, and revengeful behaviours 2.80 ±1.05 (scores in the scale 1–5). Conclusions: An image composed of many symptoms more frequent than a single symptom in the case of the participants of military actions. The diagnosis should, if possible, also cover the nature of social support because the experienced trauma may also concern the closest environment of the participant/participants of antiterrorist actions.
Keywords: externalising anger; blood pressure; hospitalisation; participants of defensive military actions